Only yours - Mallery, Susan (Don Mills, Ont. : HQN, 2011)
Surgeon Simon Bradley moves from place to place, avoiding emotional attachments and helping to heal children who need his skillful touch, is surprised to discover that, after meeting therapy dog trainer Montana Hendrix, he is in no hurry to leave Fool's Gold.
Keywords: Surgeons -- Fiction; Service dogs -- Fiction; California -- Fiction; Love stories